Pendekatan PER untuk Menilai Harga Saham dalam Pengambilan Keputusan Berinvestasi - Ulya, Badriyatul; Rachmawati, Lucky (Jurnal Ekonomika dan Bisnis Islam, 2019)
This research aims to assess the stock price as well as knowing the right investment decisions on the company’s listing in Jakarta Islamic Index (JII) using fundamental analysis approach price earning ratio (PER). This research is quantitative descriptive research. This population of the research is using companies listed on the Jakarta Islamic Index (JII) period of 2015-2017. The sampling technique in this research is using purposive sampling, with the specified criteria so there are 13 companies that made the samples on this research. The results showed that there 11 company whose shares are includeds in the category of undervalued, shares with code: ADRO, AKRA, ASII, INDF, KLBF, LPKR, LSIP, SMRA, TLKM, UNTR and UNVR then the right investment decisions is buy the stock. While the two companies whose shares are includeds in the category of overvalued, shares with code: ICBP and WIKA, then the right investment decision is to sell the stock.